Multi-core Fiber Resource Allocation Algorithm based on Crosstalk and Fragmentation - YANG Haoyu; REN Danping; DENG Yujing; HU Jinhua; ZHAO Jijun (Guangtongxin yanjiu)
【Objective】Minimizing Inter-Core Crosstalk (ICXT) between cores in Multi-Core Fiber (MCF) will increase spectrum fragmentation in network links, thereby reducing Spectrum Utilization (SU) and resulting in insufficient spectrum resources required for subsequent services. In this paper, a Crosstalk Aware and Low Fragmentation (CA-LF) based resource allocation algorithm is proposed.【Methods】In the path selection stage, to avoid the emergence of “bottleneck paths” and balance the use of resources in network links, the K Shortest Paths (KSP) algorithm is used to improve the path selection strategy by combining path nodes, path length and spectrum resource usage. In the core spectrum allocation stage, a resource allocation method that considers crosstalk and fragmentation is designed. Taking a seven-core fiber as an example, its cores are first divided into two groups: a non-adjacent core group and an adjacent core group. Within each group, the cores are then arranged in descending order according to the Core Fiber Spectral Continuity (CSC). Firstly, when allocating resources for non-adjacent core groups without considering crosstalk constraints, the proposed flexible debris metric is used to reduce spectrum debris generated during operational dismantlement and establishment. If a service is blocked for the first time in the non-adjacent core group, it will then be initiated in the adjacent core group. At this stage, adjacent cores with crosstalk constraints come into play. Here, resource allocation is determined by calculating the combined crosstalk-fragmentation effect of the spectrum block and the CSC, thereby achieving a balance between crosstalk and fragmentation.【Results】Simulation verification is carried out in NSFNET and COST239 network respectively. The results show that compared with the Low-netwXT algorithm, the CA-LF algorithm improves the SU by 6.5% and 5.7% respectively. The network Blocking Probability (BBP) and Spectrum Fragments Rate (SFR) were reduced by 6.9%, 10.8% and 9.5%, 9.3% respectively when the network load is high.【Conclusion】The CA-LF resource allocation algorithm mentioned in the article reduces the generation of fragmentation caused by crosstalk constraints, improves the utilization rate of network resources, and provides a new method for dealing with spectral fragmentation caused by crosstalk in MCFs.